Starting School Healthy and Ready to Learn: Using Social Indicators to Improve School Readiness in Los Angeles County - Cheryl Wold, MPH; Will Nicholas, PhD, MPH (Centers for Disease Control and Prevention, 2007)
BackgroundSchool readiness is an important public health outcome, determined by a set of interdependent health and developmental trajectories and influenced by a child's family, school, and community environments. The same factors that influence school readiness also influence educational success and health throughout life.ContextA California cigarette tax ballot initiative (Proposition 10) created new resources for children aged 0 to 5 years and their families statewide through county-level First 5 commissions, including First 5 LA in Los Angeles County. An opportunity to define and promote school readiness indicators was facilitated by collaborative relationships with a strong emphasis on data among First 5 LA, the Children's Planning Council, and the Los Angeles County Public Health Department, and other child-serving organizations. MethodsA workgroup developed school readiness goals and indicators based on recommendations of the National Education Goals Panel and five key domains of child well-being: 1) good health, 2) safety and survival, 3) economic well-being, 4) social and emotional well-being, and 5) education/workforce readiness.ConsequencesThe Los Angeles County Board of Supervisors and First 5 LA Commission adopted the school readiness indicators. First 5 LA incorporated the indicators into the results-based accountability framework for its strategic plan and developed a community-oriented report designed to educate and spur school readiness-oriented action. The Los Angeles County Board of Supervisors approved a countywide consensus-building plan designed to engage key stakeholders in the use of the indicators for planning, evaluation, and community-building activities.InterpretationSchool readiness indicators in Los Angeles County represent an important step forward for public health practice, namely, the successful blending of an expanded role for assessment with the ecological model.